Приключения Васи Куролесова - Коваль Юрий Иосифович (Школьная библиотека, 2009)
Экземпляры: б/ф №7 (20200921) / Инвентарный номер: 39245 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 56 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6